Misperceptions, Income Positions, and Attitudes Toward EU Inequality: A Cross-Country Survey Experiment - Elisabeth Sattler-Bublitz; Hequn Wang; Julian Jäger; Henning Lohmann; Miriam Beblo (Social Indicators Research, 2023)
We examine the relationship between misperceptions, income positions, and attitudes toward inequality at the supranational level of the EU. Conducting surveys in four EU member states (Germany, Italy, Poland, and Sweden), we confirm that Europeans misperceive their own income position in the EU. Once we account for these misperceptions, we find for all four countries that the lower their income rank, the more citizens assess EU income differences as unjust and are supportive of an EU minimum wage. When we inform a randomized subsample about their misperceived EU income position, those who learn that they are richer than they initially thought assess EU income differences as less unjust. The experiment unveils differences across countries: The general result is driven by respondents in Italy, Poland, and Sweden, whereas information on income misperceptions has opposing effects in Germany. This difference in the treatment reactions of the Germans is very robust and cannot be explained by their identification with the EU, trust in the EU, altruistic motives, political orientation, or socio-demographics.
Keywords: 300; Misperceptions; Income; Inequality; European Union; Survey experiment